2022
DOI: 10.1002/mats.202100083
|View full text |Cite
|
Sign up to set email alerts
|

A Coarse‐Grained Model for cis‐Polyisoprene: Thermal Expansion and Glass Transition Temperature

Abstract: A coarse‐grained (CG) model of cis‐1,4‐polyisoprene (cis‐PI) is developed using systematic coarse‐graining strategy. The bonded interactions of the model are captured using analytical potentials with parameters derived to match structural probability distributions of atomistic system. The nonbonded interactions are presented by Lennard‐Jones potentials with parameters specified to match the density and thermal expansion behavior obtained from experiment. The CG force field is validated through the molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…47−49 In order for the CG model to be applicable at other temperatures, it is necessary to incorporate a temperature-correction term for its potentials. 21,24,50,51 Through our parametric study, we found that the order of influence of the four nonbonded parameters on density is σ BB > σ AA > ε BB > ε AA . To keep it as simple as possible, we chose to change only one parameter of the four.…”
Section: Nonbonded Potentials and Density Optimizationmentioning
confidence: 84%
See 4 more Smart Citations
“…47−49 In order for the CG model to be applicable at other temperatures, it is necessary to incorporate a temperature-correction term for its potentials. 21,24,50,51 Through our parametric study, we found that the order of influence of the four nonbonded parameters on density is σ BB > σ AA > ε BB > ε AA . To keep it as simple as possible, we chose to change only one parameter of the four.…”
Section: Nonbonded Potentials and Density Optimizationmentioning
confidence: 84%
“…It can be seen that the initial CG model (cyan symbols) underpredicts the all-atomistic density (black symbols) at temperatures below 500 K and overpredicts the density at temperatures above 500 K. This discrepancy in the density arises from the fact that there is no chemically specific coarse-graining potential capable of capturing the target properties across a broad range of temperatures. The accuracy of CG models is usually confined to a narrow temperature range close to their calibration state, a phenomenon referred to as the transferability issue. In order for the CG model to be applicable at other temperatures, it is necessary to incorporate a temperature-correction term for its potentials. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations